Tunable Electronic Properties and Potential Applications of BSe/XS2 (X=Mo, W) van der Waals Heterostructures. Issue 10 (6th September 2020) - Zhang, Dingbo; Gao, Qiang; Chen, Yuanzheng; Xia, Yudong; Wang, Hui; Wang, Hongyan; Ni, Yuxiang
Abstract: Constructing van der Waals (vdW) heterostructures by using different 2D materials is an effective strategy to overcome the shortcoming of single 2D materials. Recently, a novel 2D material boron selenide (BSe) has been predicted, holding a hexagonal structure similar to 2D transition metal dichalcogenides (TMDs). In this paper, the MoS2 /BSe, and WS2 /BSe heterostructures are therefore constructed, finding that they are type‐II band alignment semiconductors with bandgaps of 1.46 and 1.73 eV, respectively. Moreover, an indirect‐to‐direct bandgap transition, and a band alignment transition can be achieved by applying the perpendicular external electric fields to the vdW heterostructures. In addition, the two built heterostructures have a good optical absorption (10 4 ), a broad optical absorption, and one competitive power conversion efficiencies (PCEs). The results also show that the PCE of the MoS2 /BSe heterostructures can be improved by increasing the number of BSe layers (11.63% for MoS2 –2BSe and 13.55% for MoS2 –3BSe). This study provides a practical way for BSe/TMDs vdW heterostructures in optoelectronic applications. Abstract : First‐principles calculations have been used to investigate systematically the electronic and optical properties of novel XS2 /BSe heterostructures. It is found that the XS2 /BSe heterostructures with type‐II band alignment share tunable electronic properties, superior optical absorptions, and competitive power conversion efficiencies (PCEs), offering a promising platform for the XS2 /BSe heterostructures in optoelectronic applications.